2021
DOI: 10.1111/ene.15165
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exergaming on hippocampal volume and brain‐derived neurotrophic factor levels in Parkinson’s disease

Abstract: Background and objective Cognitive impairment is among the most burdensome non‐motor symptoms in Parkinson's disease (PD) and has been associated with hippocampal atrophy. Exercise has been reported to enhance neuroplasticity in the hippocampus in correlation with an improvement of cognitive function. We present data from the Training‐PD study, which was designed to evaluate effects of an “” training protocol on neuronal plasticity in PD. Methods We initiated a 6‐week exergaming training program, combining vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 59 publications
2
11
0
1
Order By: Relevance
“…This study found a correlation between a certain amount of physical exercise and better survival in univariate analysis. In terms of molecular biology, exercise intervention exerts neuroprotective effects by resisting oxidative stress and neuroinflammation and upregulating the expression of brain-derived neurotrophic factor (BDNF) and glial cell line-derived neurotrophic factor (GDNF) in the nigrostriatal pathway [ 29 31 ]. In terms of clinical benefits, exercise intervention delays motor progression and cognitive decline in PD patients and improves their physical function and sleep quality [ 15 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study found a correlation between a certain amount of physical exercise and better survival in univariate analysis. In terms of molecular biology, exercise intervention exerts neuroprotective effects by resisting oxidative stress and neuroinflammation and upregulating the expression of brain-derived neurotrophic factor (BDNF) and glial cell line-derived neurotrophic factor (GDNF) in the nigrostriatal pathway [ 29 31 ]. In terms of clinical benefits, exercise intervention delays motor progression and cognitive decline in PD patients and improves their physical function and sleep quality [ 15 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, many studies have reported the beneficial effects of physical activity in a number of neurodegenerative diseases, underlining the neuroprotective effect of exercise [48][49][50][51]. Physical activity can indeed increase the expression of the genes involved in antioxidant defense, can counteract the debilitating effects of many pathologies of the nervous system, and can even improve cognitive functions and memory.…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies have suggested that this may be due to (1) alterations in brain structure, such as hippocampal atrophy and hippocampal neuron damage; (2) alterations in neurotransmitter signaling, such as norepinephrine, dopamine, and 5-HT systems, which are known to be affected in PD patients (and these neurotransmitters are also involved in mood regulation); (3) alterations in inflammation and brain-derived neurotrophic factor (BDNF) levels; and (4) psychosocial factors and pain, which may also contribute to the development of depression in PD patients [ 44 ]. A large part of the above-mentioned mechanisms that may contribute to the emergence of depression in PD patients is influenced by physical activity, because some studies have found evidence that physical activity may alleviate depression in PD patients by (1) protecting the hippocampal volume of the brain [ 45 ] and regenerating hippocampal neurons by decreasing glucocorticoid receptors [ 46 , 47 ]; (2) increasing tryptophan hydroxylase, supplying 5-hydroxytryptamine synthesis [ 48 ], promoting dopamine release to improve patients’ mood [ 49 ], activating the endogenous cannabinoid system, altering the hypothalamic pituitary–adrenal axis function, and increasing norepinephrine levels [ 48 ]; (3) increasing cerebral blood flow, alleviating oxidative stress and inflammation, and increasing the expression of brain-derived neurotrophic factor (BDNF) [ 50 , 51 ]; and (4) reducing disability rates and increasing patients’ quality of life [ 24 ]. It is evident that a variety of exercise programs have proven to be valid studies.…”
Section: Discussionmentioning
confidence: 99%